POSSIBILITIES FOR DEVELOPMENT OF PRESCHOOL EDUCATION IN RUSSIA WITH REGARD TO WORLD EXPERIENCE - A. Tisyachin (Publishing House of the State University of Management, 2017)
In this article a comparative assessment of the level of development of preschool education in the Russian Federation in relation to the best world samples and identified the main factors affecting the quality of preschool education. Current global trends characterized by: the introduction of the concept of universal quality control, increase the share of enrolment, the introduction of new educational programs, increase in funding. On the basis of the conducted research, the author formulated suggestions for improving the quality of preschool education in Russia taking into account international experience.